2011
DOI: 10.1021/jm2011436
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of Orphan Nuclear Receptor Small Heterodimer Partner Ligand and Apoptosis Inducer (E)-4-[3-(1-Adamantyl)-4-hydroxyphenyl]-3-chlorocinnamic Acid. 2. Impact of 3-Chloro Group Replacement on Inhibition of Proliferation and Induction of Apoptosis of Leukemia and Cancer Cell Lines

Abstract: The parent phenol of adapalene and its (E)-cinnamic acid analogue were found to induce cancer cell apoptosis but cause adverse systemic effects when administered to mice. In contrast, their respective 5-Cl- and 3-Cl-substituted analogues had their adverse effects mitigated without a comparable loss of cancer cell inhibitory activity. As a result, pharmacologic space in this region of the cinnamic phenyl ring scaffold was explored. Various substituents were introduced, and their effects on cancer cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Multiple studies revealed that when SHP specific ligands, 5-Cl-AHPN & 3-Cl-AHPC used alone or in combination, decreased cell proliferation and increased cell cycle arrest, and apoptosis in KG-1 AML cells [ 127 , 128 ]. Kim et al (2009) reported that treatment of leukemic (U937) cells with differentiation agents such as phorbol esters (PMA) have increased the levels of SHP, p21 WAF1 , and p65 of NF-κB subunits, suggesting how the expression of SHP increases the cellular survival of differentiating monocytes by transcriptional regulation of target genes of cell survival and differentiation [ 126 ].…”
Section: Nrs In Hmmentioning
confidence: 99%
“…Multiple studies revealed that when SHP specific ligands, 5-Cl-AHPN & 3-Cl-AHPC used alone or in combination, decreased cell proliferation and increased cell cycle arrest, and apoptosis in KG-1 AML cells [ 127 , 128 ]. Kim et al (2009) reported that treatment of leukemic (U937) cells with differentiation agents such as phorbol esters (PMA) have increased the levels of SHP, p21 WAF1 , and p65 of NF-κB subunits, suggesting how the expression of SHP increases the cellular survival of differentiating monocytes by transcriptional regulation of target genes of cell survival and differentiation [ 126 ].…”
Section: Nrs In Hmmentioning
confidence: 99%
“…Besides the cinnamic acid hybrids mentioned above, some other cinnamic acid conjugates also showed certain antiproliferative activity against various cancer cell lines. [ 63–77 ] For example, hybrid 34 ((2 R ,3 S ,3a S ,6a R )−2‐(( R )‐hydroxy(phenyl)methyl)−5‐oxohexahydrofuro[3,2‐ b ]furan‐3‐yl cinnamate; IC 50 : 0.12–0.85 µM, MTT assay) was highly potent against K562, Jurkat, MCF‐7, and HeLa cancer cell lines and the activity was slightly lower than that of doxorubicin (IC 50 : 0.03–0.25 µM). [ 77 ] However, the majority of the rest of the cinnamic acid hybrids were far inferior to the references drugs in terms of antiproliferative activity.…”
Section: Cinnamic Acid Hybridsmentioning
confidence: 99%
“…This ligand-dependent activation was shown to repress certain CYP enzymes involved in bile acid regulation. Additional studies are also exposing further potential synthetic ligands that could be utilized to modulate SHP activity and its repressive functions (Xia et al, 2011, 2012). …”
Section: Atypical Receptors and Receptor-like Proteinsmentioning
confidence: 99%